ANALISIS DAYASAING KOMODITAS UNGGULAN PERIKANAN TANGKAP KABUPATEN SUKABUMI - Achmad Fadillah; Yusalina Yusalina (Magister Science of Agribusiness, Department of Agribusiness, FEM-IPB University, 2011)
Fisheries sector in Sukabumi can take potential role to act as the prime mover in developing the regional economy. However, its potency has not been optimized properly. It is expected that the low economic performance of fisheries sector are caused by the comparative advantage that was not fully transformed into competitive advantage. This study aims toidentify fisheries commodity that can be a superior comodity in Sukabumi and to analyze the competitiveness of superior fisheries commodity in Sukabumi. The analytical tools used in this research are Location Quotient (LQ) and Porter's Diamond Theory. The results of study show that: (1) Kuwe, Tembang, Lisong, Cakalang, Albakora, Madidihang, Tuna Mata Besar, Layur, Kakap Putih, and Belanak have a comparative advantage in Sukabumi, and (2) superior fisheries commodity in Sukabumi do not have optimal competitiveness because there are constraints within each component of competitiveness. However, all these obstacles can be overcome with the role of government and the role of opportunities that support the advancement of fisheries sector.